2019
DOI: 10.18203/2320-6012.ijrms20195520
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levobupivacaine vs bupivacaine in thoracic spinal anaesthesia for laparoscopic cholecystectomies

Abstract: Background: Levobupivacaine is the pure S enantiomer of racemic bupivacaine. It is a long acting variant that is less toxic to the heart and central nervous system. It has gained relevance and popularity in the modern anaesthetic practice. Thoracic spinal anaesthesia has been shown to an effective   and safe anaesthetic approach for a varied spectrum of surgeries including laparoscopic cholecystectomies.  Incorporation   of epidural catheter adds flexibility and the provision of postoperative analgesia. To ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Kour et a conducted a study to compare the efficacy of levobupivacaine and bupivacaine in thoracic combined spinal epidural anaesthesia for laparoscopic cholecystectomies. 14 The authors found mean sensory block time to be more in bupivacaine group as compared to Ropivacaine group and the difference was found to be statistically significant (p<0.05). Similar longer duration of Bupivacaine group was also reported by the authors such as Kaur et al and Malinovsky et al 15,16…”
Section: Discussionmentioning
confidence: 90%
“…Kour et a conducted a study to compare the efficacy of levobupivacaine and bupivacaine in thoracic combined spinal epidural anaesthesia for laparoscopic cholecystectomies. 14 The authors found mean sensory block time to be more in bupivacaine group as compared to Ropivacaine group and the difference was found to be statistically significant (p<0.05). Similar longer duration of Bupivacaine group was also reported by the authors such as Kaur et al and Malinovsky et al 15,16…”
Section: Discussionmentioning
confidence: 90%
“…Narmatha Yangste etal [6]have used isobaric levobupivacaine for Thoracic segmental spinal anaesthesia for LSCS & stated that levobupivacaine is better alternative to bupivacaine. (6) In contrast to open surgery, laproscopy procedure requires only very little incisions and has benefits such as less pain and shorter hospital stay due to less tissue damage and swift return to everyday life due to fast recovery [7]. However, considerable difficulties in anesthetic management could be encountered since wide hemodynamic fluctuation may develop due to pneumoperitoneum and position changes.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%